BETWEEN WORK AND SPIRITUALITY: Exploring Indonesian Female Migrant Workers’ Engagement with Islamic Study Sessions in Taiwan (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
This study delves into the spiritual lives of Indonesian female migrant workers in Taiwan. It uncovers how these workers actively engage in pengajian (Islamic study sessions) to address spiritual needs. The research question in this study is how do pengajian contribute to fulfilling spiritual needs, strengthening communication networks, and forming national identity for Indonesian women migrant workers in Taiwan. This research uses a qualitative approach with an online data collection method, involving in-depth interviews with the management of the pengajian and participatory observation of its activities of Indonesian women migrant workers in Taiwan. The research reveals that these gatherings facilitate everyday Islamic jurisprudence studies, sufism moral introspection, Quranic learning, and salawat recitations. Additionally, these sessions foster robust communication networks among workers, enhancing their information exchange, relationships, and discussions. In uncertain conditions, these gatherings provide ideological reinforcement, social engagement, and a sense of national identity. The study suggests potential future research avenues in education and political ideology of these migrant workers.